Vaginal Delivery in Women With a Low-lying Placenta: A Systematic Review and Meta-analysis. Issue 2 (June 2020) - Jansen, C.; de Mooij, Y.M.; Blomaard, C.M.; Derks, J.B.; van Leeuwen, E.; Limpens, J.; Schuit, E.; Mol, B.W.; Pajkrt, E.
Abstract : ( BJOG . 2019;126:1118–1126) While physicians strive to avoid unnecessary cesarean sections, they must weigh this goal with the possible risks of hemorrhage in patients with low-lying placentas. Guidelines and recommendations vary widely on whether patients with low-lying placentas should deliver by cesarean delivery. The Royal College of Obstetricians and Gynaecologists states patients with a low-lying placenta should deliver via cesarean, while in the Netherlands, vaginal delivery is suggested for patients with an internal os distance (IOD) of >10 mm. This systematic review and meta-analysis aimed to evaluate the possibility of successful vaginal delivery with a low-lying placenta.